2015
DOI: 10.1016/j.biomaterials.2015.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of puberty in mice following decellularized ovary transplant

Abstract: Clinical interventions to preserve fertility and restore hormone levels in female patients with therapy-induced ovarian failure are insufficient, particularly for pediatric cancer patients. Laproscopic isolation of cortical ovarian tissue followed by cryopreservation with subsequent autotransplantation has temporarily restored fertility in at least 27 women who survived cancer, and aided in pubertal transition for one pediatric patient. However, reintroducing cancer cells through ovarian transplantation has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
169
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(192 citation statements)
references
References 46 publications
8
169
0
1
Order By: Relevance
“…[21][22][23][24] In 2015, the first D-ovary platform was successfully obtained and it partly restored endocrine functions in a mouse model. 15 However, some limitations existed in that method. First, the long SDS process has a strong damaging effect was demonstrated on the ultrastructure of the native tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24] In 2015, the first D-ovary platform was successfully obtained and it partly restored endocrine functions in a mouse model. 15 However, some limitations existed in that method. First, the long SDS process has a strong damaging effect was demonstrated on the ultrastructure of the native tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, decellularized ECM was successfully harvested from a bovine ovary for the first time. 15 The study provided the initial step of creating an artificial ovary and introduced a novel therapy for ovariectomized mice. However, longterm sodium dodecyl sulfate (SDS) treatment in the study has been reported to have a strong damaging effect on the ultrastructure of native tissue and be cytotoxic.…”
Section: Introductionmentioning
confidence: 99%
“…They stated that ECM enhances the growth and differentiation of the somatic cells of the follicle, also the meiotic competence of the oocyte, thus providing good quality eggs. Furthermore, it has been recently shown that ECM is a very important structure in maintaining follicle viability in terms of ovarian transplantation [20]. Decellularization made by leaving the ECM in place and followed by recellularization with primary ovarian cells was performed successfully in that experimental study.…”
Section: Discussionmentioning
confidence: 76%
“…Laronda et al [46] constructed scaffolds from decellularized bovine and human ovarian tissue to graft primary murine ovarian cells. These recellularized matrices were able to initiate puberty in host ovariectomized mice.…”
Section: Decellularized Ovarian Ecmmentioning
confidence: 99%